Вітаміноносні шипшини Національного дендрологічного парку “Софіївка” - Denisko, I.L. (M.M. Gryshko National Botanical Garden of the NAS of Ukraine, 2006)
The characteristics of the vitamin bеaring species and forms of Rosa L. introducted in the conditions of the dendrological park Sofiyivka are given in the article.